2020
DOI: 10.1029/2019jb018604
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Granular Aggregates: Static and Dynamic Bulk Moduli

Abstract: Sand and glass bead samples were monotonically loaded from 0 to 50 MPa and then monotonically unloaded, all under hydrostatic stress conditions. Sand deformed irreversibly and its porosity loss was permanent. In contrast, the glass bead deformation was almost fully reversible with the initial porosity recovered. During loading, the static bulk modulus in all sand samples increased from 0 to about 0.5 GPa between 0-and 15-MPa stress and remained constant for the remainder of the loading. Such behavior, somewhat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…p instead of the bulk modulus K. The functional form in this theory is the same as that in Gassmann's: Figure 5 shows an example of the results of fluid substitution (pure water) on the elastic properties of high-porosity sand measured in the laboratory [11] at roomdry conditions. Clearly, the pore fluid has a dramatic effect on Poisson's ratio.…”
Section: Effect Of Pore Fluid On Elastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…p instead of the bulk modulus K. The functional form in this theory is the same as that in Gassmann's: Figure 5 shows an example of the results of fluid substitution (pure water) on the elastic properties of high-porosity sand measured in the laboratory [11] at roomdry conditions. Clearly, the pore fluid has a dramatic effect on Poisson's ratio.…”
Section: Effect Of Pore Fluid On Elastic Propertiesmentioning
confidence: 99%
“…Both Eqs. (11) and (12) were discovered by Archie in 1942 [6] and remain the cornerstone of resistivity interpretation for hydrocarbon saturation in the wellbore. Various modifications of these equations dealing with resistivity interpretation in sediments containing clays and shales are discussed in Mavko et al [1].…”
Section: Introduction: Subject Of Rock Physics Background and Briefmentioning
confidence: 99%
“…This final step is more difficult than it may appear at first glance due to physical and geometric constraints. Since the wave speed in the steel block containing the sensors (3,250 m/s) is much larger than that of the fault gouge (570 m/s; e.g., Domenico, 1977; Muqtadir et al, 2020), ray theoretical arguments imply that any ray arriving at one of the sensors must have been traveling near vertically in the gouge layer, as the critical angle from gouge to steel is of order 10°. This constraint accentuates the traditional tradeoff between event depth and origin time to the extent that we have essentially zero depth resolution in the gouge.…”
Section: Methodsmentioning
confidence: 99%
“…Zimmer [12] applied corrections to the axial strain for the strain gauge hysteresis and the end effects when measuring lab-repacked loose sand samples. Muqtadir et al [34] reported that the radial LVDT gauges in their triaxial testing system failed to track a large displacement when measuring repacked loose sands from Saudi Arabia. Additional corrections are required to obtain reasonable strain data.…”
Section: Introductionmentioning
confidence: 99%